Stereotactic and Robotic Minimally Invasive Thermal Ablation of Malignant Liver Tumors: A Systematic Review and Meta-Analysis - Tinguely, Pascale; Paolucci, Iwan; Ruiter, Simeon J. S.; Weber, Stefan; de Jong, Koert P.; Candinas, Daniel; Freedman, Jacob; Engstrand, Jennie (Frontiers in Oncology, 2021)
Background Stereotactic navigation techniques aim to enhance treatment precision and safety in minimally invasive thermal ablation of liver tumors. We qualitatively reviewed and quantitatively summarized the available literature on procedural and clinical outcomes after stereotactic navigated ablation of malignant liver tumors. Methods A systematic literature search was performed on procedural and clinical outcomes when using stereotactic or robotic navigation for laparoscopic or percutaneous thermal ablation. The online databases Medline, Embase, and Cochrane Library were searched. Endpoints included targeting accuracy, procedural efficiency, and treatment efficacy outcomes. Meta-analysis including subgroup analyses was performed. Results Thirty-four studies (two randomized controlled trials, three prospective cohort studies, 29 case series) were qualitatively analyzed, and 22 studies were included for meta-analysis. Weighted average lateral targeting error was 3.7 mm (CI 3.2, 4.2), with all four comparative studies showing enhanced targeting accuracy compared to free-hand targeting. Weighted average overall complications, major complications, and mortality were 11.4% (6.7, 16.1), 3.4% (2.1, 5.1), and 0.8% (0.5, 1.3). Pooled estimates of primary technique efficacy were 94% (89, 97) if assessed at 1–6 weeks and 90% (87, 93) if assessed at 6–12 weeks post ablation, with remaining between-study heterogeneity. Primary technique efficacy was significantly enhanced in stereotactic vs. free-hand targeting, with odds ratio (OR) of 1.9 (1.2, 3.2) (n = 6 studies). Conclusions Advances in stereotactic navigation technologies allow highly precise and safe tumor targeting, leading to enhanced primary treatment efficacy. The use of varying definitions and terminology of safety and efficacy limits comparability among studies, highlighting the crucial need for further standardization of follow-up definitions.